Hydrogenated boronene / pvdf composite lithium metal battery negative electrode and preparation method and application thereof

CN123017898APending Publication Date: 2026-10-30ZHENGZHOU BAK ELECTRONICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610919309.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]但是目前,氢化硼烯在锂金属电池领域的应用研究尚处于起步阶段,尚未见将氢化硼烯与高纯度锂电级PVDF复合,利用两者协同作用构建锂金属电池负极界面修饰层,实现锂枝晶高效抑制、界面稳定性提升及电池性能优化的相关方法

Benefits of technology

1、本发明利用氢化硼烯的亲锂性和均匀成核位点,引导锂金属均匀沉积,从根源上抑制枝晶生长,同时利用PVDF原位生成LiF稳定SEI膜,并利用其高介电性降低枝晶尖端电荷,且氢化硼烯的高机械强度可增强复合修饰层的抗刺穿能力,抵御锂枝晶的机械破坏,PVDF的柔韧性可缓冲体积膨胀,减少界面开裂,将两者协同作用,抑制效果优于单一材料及现有复合体系,实现了界面刚性与柔性的平衡;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017898A_ABST
    Figure CN123017898A_ABST
Patent Text Reader

Abstract

The application discloses a boron hydride-ene / PVDF composite lithium metal battery negative electrode and a preparation method and application thereof, relates to the technical field of lithium metal batteries, and the negative electrode comprises a lithium metal substrate and a composite modification layer coated on the surface of the lithium metal substrate. The preparation method comprises the following steps: obtaining pretreated boron hydride-ene, a lithium metal substrate, a conductive additive and a PVDF mother liquor; adding the pretreated boron hyydride-ene and the conductive additive into the PVDF mother liquor, stirring and ultrasonic dispersing to obtain a composite slurry; coating the composite slurry on the surface of the pretreated lithium metal substrate; adopting a gradient temperature rising drying mode to prepare a semi-finished negative electrode sheet; performing sheet pressing treatment on the semi-finished negative electrode sheet; cooling the negative electrode sheet to room temperature, and obtaining a finished negative electrode after cutting and packaging. The application utilizes the synergistic advantages of boron hydride-ene and PVDF, solves the problem of defects of single materials, stabilizes an SEI film, relieves volume expansion, realizes effective inhibition of lithium dendrites, improves interface stability and optimizes battery performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium metal battery technology, specifically to a boronene / PVDF composite lithium metal battery anode, its preparation method, and its application. Background Technology

[0002] Lithium metal batteries, due to their extremely high theoretical specific capacity (3860 mAh / g) and the lowest redox potential (-3.04 Vvs SHE), are considered core candidates for next-generation high-energy-density energy storage devices, with irreplaceable application prospects in electric vehicles, large-scale energy storage power stations, and other fields. However, three major challenges faced by lithium metal anodes during charge and discharge severely restrict their industrialization process: First, lithium dendrite growth, which can pierce the battery separator, leading to internal short circuits, thermal runaway, and safety hazards; second, interface instability, where the growth and shedding of lithium dendrites can damage the solid electrolyte interphase (SEI) film, producing "dead lithium" and reducing the battery's coulombic efficiency; and third, volume expansion, where the volume change of lithium metal during charge and discharge can reach over 300%, leading to electrode cracking and interface peeling, further shortening the battery's cycle life.

[0003] To address the aforementioned issues, various lithium dendrite suppression strategies have been proposed in existing technologies. Among these, anode interface modification has become a research hotspot due to its simplicity and significant effects. Polyvinylidene fluoride (PVDF), a commonly used binder and interface modification material in the lithium battery field, possesses excellent chemical stability, thermal stability, electrochemical inertness, and film-forming properties. The carbon-fluorine bonds in its molecular structure can generate a LiF protective layer in situ during battery charging and discharging, which helps stabilize the SEI film and alleviate lithium dendrite growth. However, when PVDF is used alone as an interface modification layer, it suffers from insufficient mechanical strength and poor ionic conductivity, making it difficult to effectively resist lithium dendrite penetration. Furthermore, it cannot provide uniform nucleation sites for lithium ions, resulting in the continued occurrence of lithium dendrite growth and failing to meet the long-term cycling requirements of high-energy-density lithium metal batteries.

[0004] Hydrogenated borophene, also known as borane or boronide, is a novel two-dimensional layered material obtained by hydrogenation modification of borene. It possesses high mechanical strength, excellent ionic conductivity, good lithiophilicity, and electronic conductivity. Its two-dimensional layered structure can serve as a site for uniform lithium ion nucleation, guiding the uniform deposition of lithium metal and inhibiting lithium dendrite growth at its source. At the same time, its high mechanical strength can enhance the puncture resistance of the interface layer and alleviate the interface damage caused by the volume expansion of lithium metal. Furthermore, hydrogenation modification can effectively solve the problem of poor stability of pure borene, broadening its application prospects in the battery field.

[0005] However, research on the application of boronene in lithium metal batteries is still in its early stages. There are currently no methods to combine boronene with high-purity lithium-grade PVDF to construct a lithium metal battery anode interface modification layer, achieving efficient suppression of lithium dendrites, improved interface stability, and optimized battery performance. In existing technologies, PVDF is often combined with oxides (LiAlO2, LATP), MOFs, carbon materials, etc., which have limited effectiveness in suppressing lithium dendrites and cannot balance interface rigidity and flexibility. Meanwhile, a single boronene modification layer suffers from insufficient flexibility and poor interface adhesion, easily leading to cracking and peeling, and failing to meet long-term cycling requirements.

[0006] Based on this, a boronene / PVDF composite lithium metal battery anode and its preparation method and application are provided, which can eliminate the drawbacks of existing technical solutions. Summary of the Invention

[0007] The purpose of this invention is to provide a boronene / PVDF composite lithium metal battery anode, its preparation method, and its application, in order to solve the problems in the background art.

[0008] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a boronide / PVDF composite lithium metal battery anode specifically includes the following steps: Step S1, Raw material pretreatment: Borobenzene powder is placed in a vacuum drying oven. After the drying operation, pretreated borobenzene is obtained. Lithium-ion grade PVDF powder is dissolved in an organic solvent and stirred until PVDF is completely dissolved and there are no obvious particles to obtain PVDF mother liquor. Lithium metal foil is cut into a preset size, ultrasonically cleaned with anhydrous ethanol, and dried in a vacuum drying oven to obtain pretreated lithium metal substrate. It is then transferred to a glove box protected by inert gas for later use. Conductive additive is placed in a vacuum drying oven and dried to obtain pretreated conductive additive. Step S2, preparation of composite slurry: add pretreated boronene and pretreated conductive additive to PVDF mother liquor, stir to disperse boronene and conductive additive in PVDF mother liquor, and then disperse by ultrasonication to obtain a uniformly dispersed composite slurry without agglomeration. Step S3, Coating: The composite slurry is uniformly coated onto the surface of the pretreated lithium metal substrate by means of scraper coating, spraying or dipping. The coating process is carried out in a glove box protected by inert gas. Step S4, Drying: Place the coated lithium metal substrate into a vacuum drying oven and use a gradient temperature drying method to remove residual solvent, so as to obtain a semi-finished negative electrode sheet with a smooth surface and no bubbles. Step S5, tableting: Under inert gas protection, the dried semi-finished negative electrode sheet is tableted using a flatbed tablet press to increase the bonding tightness between the composite modification layer and the lithium metal substrate. The composite modification layer is formed by coating a composite slurry. Step S6, Finished Product Processing: The negative electrode sheet after compression is placed in a glove box protected by inert gas and cooled to room temperature. After cutting and packaging, the finished product of hydride boronene / PVDF composite lithium metal battery negative electrode is obtained.

[0009] Further, the raw material pretreatment in step S1 specifically includes boronene pretreatment, PVDF mother liquor preparation, lithium metal substrate pretreatment, and conductive additive pretreatment, specifically including: Pretreatment of hydroborene: The hydroborene powder is placed in a vacuum drying oven and dried for 8h to 24h at a temperature of 60℃~120℃ and a vacuum degree of ≤10Pa to remove the moisture and impurities adsorbed on the surface of the hydroborene powder. After the drying operation is completed, the pretreated hydroborene is obtained. Preparation of PVDF mother liquor: Lithium-ion grade PVDF powder is dissolved in an organic solvent and stirred for 2 to 6 hours at a temperature of 60℃ to 80℃ and a stirring speed of 300 r / min to 800 r / min. After stirring until the PVDF is completely dissolved and there are no obvious particles, it is allowed to stand for 1 to 2 hours to prepare a PVDF mother liquor with a mass concentration of 5% to 20%. Lithium metal substrate pretreatment: The lithium metal foil is cut into a preset size and ultrasonically cleaned in anhydrous ethanol for 5 min to 15 min under an ultrasonic power of 100W to 300W to remove the oxide layer and oil on the surface of the lithium metal foil. Then it is placed in a vacuum drying oven and dried at a temperature of 40℃ to 60℃ for 2 h to 4 h. After drying, the pretreated lithium metal substrate is obtained and transferred to a glove box protected by inert gas for later use. Conductive additive pretreatment: The conductive additive is placed in a vacuum drying oven and dried at a temperature of 80℃~100℃ for 4h~8h to remove the surface moisture of the conductive additive. After the drying operation is completed, the pretreated conductive additive is obtained.

[0010] Further, the preparation of the composite slurry in step S2 specifically includes: adding pretreated boronene and pretreated conductive additive to the PVDF mother liquor, stirring for 2h to 6h at room temperature and a stirring speed of 500r / min to 1000r / min, so that the boronene and conductive additive are dispersed in the PVDF mother liquor, and then ultrasonically dispersing for 1h to 3h at an ultrasonic power of 100W to 500W, with a 10min pause every 30min of ultrasonic dispersion, to obtain a uniformly dispersed composite slurry without agglomeration after ultrasonic dispersion, wherein the room temperature is 20 to 25℃.

[0011] Further, the coating in step S3 specifically includes: uniformly coating the composite slurry onto the surface of the pretreated lithium metal substrate by means of scraper coating, spraying or dipping, the coating process is carried out in a glove box under inert gas protection, and the thickness of the composite modification layer after coating is controlled at 1μm~20μm; Specifically, when using a scraper for coating, the scraper gap is 10μm~40μm and the coating speed is 5mm / s~15mm / s. When using a spray gun, the spray gun pressure is 0.1MPa~0.3MPa, the spraying distance is 10cm~20cm, and the spraying speed is 8mm / s~12mm / s. When using a dip coating, the immersion time is 10s~30s and the lifting speed is 5mm / s~10mm / s.

[0012] Furthermore, the gradient temperature drying in step S4 specifically includes: Drying at 60℃~80℃ for 4h~6h removes most of the solvent; Drying at 100℃~150℃ and vacuum degree ≤10Pa for 8h~18h is used to remove residual solvent and obtain a semi-finished negative electrode sheet with a smooth surface and no bubbles. During the drying process, the temperature rise rate is controlled at 5℃ / min to 10℃ / min.

[0013] Furthermore, in step S5, the pressure of tableting is 0.5MPa~5MPa, the tableting time is 10min~30min, and the porosity of the composite modified layer after tableting is controlled at 10%~50%.

[0014] Furthermore, the organic solvent is one or more of N-methylpyrrolidone, dimethylformamide, or dimethyl sulfoxide.

[0015] A boronene / PVDF composite lithium metal battery anode is prepared by the above-mentioned preparation method. The anode includes a lithium metal substrate and a composite modification layer coated on the surface of the lithium metal substrate. The thickness of the composite modification layer is 1μm~20μm, the porosity is 10%~50%, and the pore size is 50nm~500nm.

[0016] Furthermore, the composite modification layer is composed of boronide, PVDF and conductive additives, wherein the boronide has a mass percentage of 15wt% to 25wt%, the PVDF has a mass percentage of 72wt% to 85wt%, and the conductive additive has a mass percentage of 0 to 3wt%, wherein the conductive additive is one of conductive carbon black or carbon nanotubes.

[0017] An application of a boronide / PVDF composite lithium metal battery anode prepared according to a certain method in the field of lithium metal batteries is used to suppress lithium dendrite growth, alleviate lithium metal volume expansion, and stabilize the solid electrolyte interface film during the charging and discharging process of lithium metal batteries.

[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention utilizes the lithiophilicity and uniform nucleation sites of borohydride to guide the uniform deposition of lithium metal, thereby inhibiting dendrite growth from the source. At the same time, it utilizes PVDF to generate a LiF-stabilized SEI film in situ and uses its high dielectric properties to reduce the charge at the dendrite tips. Furthermore, the high mechanical strength of borohydride can enhance the puncture resistance of the composite modification layer and resist the mechanical damage of lithium dendrites. The flexibility of PVDF can buffer volume expansion and reduce interface cracking. The synergistic effect of the two is better than that of single materials and existing composite systems, achieving a balance between interface rigidity and flexibility. 2. The preparation method of the present invention adopts conventional coating and drying processes, without the need for complex equipment and harsh reaction conditions. The raw materials can all be obtained through industrial production. Moreover, PVDF is a mature material in the lithium battery field with a high localization rate, which can reduce the cost of raw materials. The entire preparation process can be mass-produced and is suitable for industrial applications. Attached Figure Description

[0019] Figure 1 This is a schematic diagram of the steps of the present invention. Detailed Implementation

[0020] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments.

[0021] Considering that in existing technologies, PVDF is often combined with oxides (LiAlO2, LATP), MOFs, carbon materials, etc., its effect on suppressing lithium dendrites is limited: at a current density of 0.5 mA / cm², the coulombic efficiency is mostly below 95% after 100 cycles, and the capacity retention rate is below 70% after 500 cycles. Moreover, it cannot balance the rigidity and flexibility of the interface, and problems such as interface cracking and delamination of the modification layer are prone to occur during cycling. On the other hand, the single hydride boronene modification layer has the problems of insufficient flexibility and poor interface adhesion (interface adhesion ≤1.0N / cm). Under the effect of lithium metal volume expansion, obvious cracking and delamination occur after 50 cycles, which cannot meet the long-term cycling requirements. Therefore, this invention designs a hydride boronene / PVDF composite lithium metal battery anode, which utilizes the synergistic advantages of hydride boronene and high-purity lithium-grade PVDF to solve the defects of single materials, stabilize the SEI film, alleviate volume expansion, and achieve effective suppression of lithium dendrites, improvement of interface stability, and optimization of battery performance. The specific technical solution is as follows.

[0022] like Figure 1 As shown, this invention provides a method for preparing a boronene / PVDF composite lithium metal battery anode, specifically including the following steps: Step S1, Raw material pretreatment: Place boronene powder in a vacuum drying oven. After drying, pretreated boronene is obtained. Dissolve lithium-ion grade PVDF powder in an organic solvent and stir until PVDF is completely dissolved and there are no obvious particles to obtain PVDF mother liquor. Cut lithium metal foil into a preset size, ultrasonically clean it with anhydrous ethanol, and dry it in a vacuum drying oven to obtain pretreated lithium metal substrate. Transfer it to a glove box protected by inert gas for later use. Place conductive additive in a vacuum drying oven. After drying, pretreated conductive additive is obtained. The drying temperature, time and vacuum degree of raw material pretreatment must be strictly controlled to avoid moisture and impurities affecting battery performance. Step S2, Preparation of composite slurry: Add the pretreated boron ene and the pretreated conductive additive to the PVDF mother liquor, stir to disperse the boron ene and the conductive additive in the PVDF mother liquor, and then ultrasonically disperse to obtain a uniformly dispersed composite slurry without agglomeration. The stirring and ultrasonic dispersion of the composite slurry must be sufficient to ensure that each component is uniformly dispersed and without agglomeration. Step S3, Coating: The composite slurry is uniformly coated onto the pretreated lithium metal substrate surface using a scraper coating, spraying, or dip coating method. The coating process is carried out in a glove box under inert gas protection to avoid oxidation of boron hydride and moisture absorption of the composite slurry. Step S4, Drying: Place the coated lithium metal substrate into a vacuum drying oven and use a gradient temperature drying method to remove residual solvent, so as to obtain a semi-finished negative electrode sheet with a smooth surface and no bubbles. Gradient temperature drying can effectively remove solvent and avoid defects such as bubbles and cracks in the composite modification layer. Step S5, tableting: Under inert gas protection, the dried semi-finished negative electrode sheet is tableted using a flatbed tablet press to increase the bonding tightness between the composite modification layer and the lithium metal substrate. The composite modification layer is formed by coating a composite slurry. Step S6, Finished Product Processing: The negative electrode sheet after compression is placed in a glove box protected by inert gas and cooled to room temperature. After cutting and packaging, the finished product of hydride boronene / PVDF composite lithium metal battery negative electrode is obtained.

[0023] Specifically, in step S1, the raw material pretreatment includes boronene pretreatment, PVDF mother liquor preparation, lithium metal substrate pretreatment, and conductive additive pretreatment, specifically including: Pretreatment of hydroborene: Place hydroborene powder in a vacuum drying oven and dry it for 8h~24h at a temperature of 60℃~120℃ and a vacuum degree ≤10Pa to remove the moisture and impurities adsorbed on the surface of the hydroborene powder. After the drying operation, the pretreated hydroborene is obtained. It is preferred to dry it for 12h at a temperature of 100℃ and a vacuum degree ≤5Pa. After drying, it should be sealed and stored to prevent oxidation. Preparation of PVDF mother liquor: Lithium-ion grade PVDF powder is dissolved in an organic solvent and stirred for 2-6 hours at a temperature of 60℃~80℃ and a stirring speed of 300r / min~800r / min until the PVDF is completely dissolved and there are no obvious particles. After standing for 1-2 hours, a PVDF mother liquor with a mass concentration of 5%~20% is prepared. It is preferred to stir for 4 hours at a temperature of 70℃ and a stirring speed of 500r / min. The preferred mass concentration is 10%~15%. The organic solvent is one or more of N-methylpyrrolidone (NMP), dimethylformamide (DMF) or dimethyl sulfoxide (DMSO). NMP is preferred because it has good compatibility with PVDF and is easy to remove by subsequent vacuum drying. The solvent purity is ≥99.9% and the moisture content is ≤300ppm. Lithium metal substrate pretreatment: Cut lithium metal foil into a preset size (e.g., 12mm×12mm, suitable for CR2032 button cell battery), and ultrasonically clean it in anhydrous ethanol for 5min~15min under ultrasonic power of 100W~300W to remove the oxide layer and oil on the surface of lithium metal foil. Then place it in a vacuum drying oven and dry it at 40℃~60℃ for 2h~4h. After drying, the pretreated lithium metal substrate is obtained and transferred to a glove box protected by inert gas (argon or nitrogen) for later use to prevent re-oxidation. Conductive additive pretreatment: The conductive additive is placed in a vacuum drying oven and dried at a temperature of 80℃~100℃ for 4h~8h to remove the surface moisture of the conductive additive. After the drying operation is completed, the pretreated conductive additive is obtained.

[0024] Specifically, in step S2, the preparation of the composite slurry includes: adding pretreated boronene and pretreated conductive additives to the PVDF mother liquor, stirring for 2 to 6 hours at room temperature and a stirring speed of 500 r / min to 1000 r / min, preferably stirring for 4 hours at a temperature of 20 to 25°C and a stirring speed of 800 r / min, to disperse the boronene and conductive additives in the PVDF mother liquor, and then ultrasonically dispersing for 1 to 3 hours at an ultrasonic power of 100 W to 500 W, preferably ultrasonically dispersing for 2 hours at an ultrasonic power of 300 W, with a 10-minute pause every 30 minutes of ultrasonic dispersion to avoid overheating of the ultrasonic process leading to PVDF degradation or oxidation of the boronene. After ultrasonic dispersion, a uniformly dispersed composite slurry without agglomeration is obtained. Finally, the viscosity of the composite slurry is 500 mPa·s to 2000 mPa·s, which is the result of a rotational viscometer test at 25°C, where the room temperature is 20 to 25°C.

[0025] Specifically, in step S3, the coating process includes: uniformly coating the composite slurry onto the pretreated lithium metal substrate surface using a doctor blade coating, spraying, or dip coating method. The coating process is carried out in a glove box protected by inert gas to prevent the composite slurry from contacting air and moisture. The thickness of the composite modification layer after coating is controlled between 1 μm and 20 μm, preferably between 5 μm and 15 μm. When using a doctor blade coating, the doctor blade gap is 10 μm to 40 μm, and the coating speed is 5 mm / s to 15 mm / s, preferably 10 mm / s, to ensure uniform coating thickness. When using a spraying method, the spray gun pressure is 0.1 MPa to 0.3 MPa, the spraying distance is 10 cm to 20 cm, and the spraying speed is 8 mm / s to 12 mm / s. When using a dip coating method, the immersion time is 10 s to 30 s, and the lifting speed is 5 mm / s to 10 mm / s.

[0026] Specifically, in step S4, the gradient temperature drying includes: Drying at 60℃~80℃ for 4h~6h removes most of the solvent; The negative electrode sheet is dried for 8-18 hours at a temperature of 100℃~150℃ and a vacuum degree ≤10Pa to remove residual solvent, resulting in a semi-finished negative electrode sheet with a smooth surface, no bubbles, and a tight bond between the composite modification layer and the lithium metal substrate. It is preferred to dry it for 12 hours at a temperature of 120℃ and a vacuum degree ≤5Pa. During the drying process, the temperature rise rate is controlled at 5℃ / min~10℃ / min to avoid rapid solvent evaporation, which could lead to bubbles or cracking.

[0027] Specifically, in step S5, the tableting pressure is 0.5MPa~5MPa, the tableting time is 10min~30min, preferably 20min, so that the composite modification layer and the lithium metal substrate are more tightly bonded, improving the interfacial adhesion and the mechanical strength of the composite modification layer. After tableting, the porosity of the composite modification layer is controlled at 10%~50%, preferably 20%~40%.

[0028] The present invention also provides a boronene / PVDF composite lithium metal battery anode, which is prepared by the preparation method described above. The anode includes a lithium metal substrate and a composite modification layer coated on the surface of the lithium metal substrate. The composite modification layer is uniformly coated on one or both sides of the lithium metal substrate to form a two-layer structure of "lithium metal substrate-composite modification layer". The thickness of the composite modification layer is 1μm~20μm, preferably 5μm~15μm, with a thickness deviation ≤±0.1μm, a porosity of 10%~50%, preferably 20%~40%, and a pore size of 50nm~500nm. It is used to provide a fast transport channel for lithium ions and buffer the volume expansion of lithium metal. The composite modification layer can be any one of a uniform mixed structure, a gradient structure, or a core-shell structure, with a uniform mixed structure being preferred. When the composite modification layer is a uniform mixed structure, it is composed of hydroborene, PVDF, and conductive additives. This structure forms a continuous three-dimensional network structure, which can provide a fast transport channel for lithium ions and a uniform nucleation site for lithium metal deposition. At the same time, it ensures a balance between the mechanical strength and flexibility of the composite modification layer. The mass percentage of hydroborene is 15wt%~25wt%, the mass percentage of PVDF is 72wt%~85wt%, and the mass percentage of conductive additives is 0~3wt%. When the content of conductive additives is greater than 0, the conductive additives are either conductive carbon black or carbon nanotubes.

[0029] This invention also provides an application of the boronide / PVDF composite lithium metal battery anode prepared according to the preparation method in the field of lithium metal batteries, which is used to suppress lithium dendrite growth, alleviate lithium metal volume expansion, and stabilize the solid electrolyte interface film during the charging and discharging process of lithium metal batteries.

[0030] To further demonstrate the application value of the boronide / PVDF composite lithium metal battery anode and its preparation method in this invention, we now provide experimental data for preparing corresponding anodes and batteries with different parameters, and conduct comparative tests. The battery structure and performance test conditions are shown below.

[0031] Battery assembly: Both the examples and comparative examples used CR2032 coin cells, with NCM811 as the positive electrode (mass load of 2 mg / cm²), Celgard 2400 as the separator, and 1M LiPF6 / EC:DMC:EMC as the electrolyte, with a volume ratio of EC:DMC:EMC of 1:1:1. After assembly, the batteries were allowed to stand for 12 hours before performance testing. Performance Testing: Electrochemical performance was tested at a constant temperature of 25℃. Coulombic efficiency was tested using deposition / stripping mode with a current density of 0.5 mA / cm² and a deposition / stripping capacity of 1 mAh / cm². Cycle stability was tested using a 0.5C charge / discharge rate with a charging cutoff voltage of 4.2V and a discharging cutoff voltage of 2.7V. Interface impedance was tested using AC impedance spectroscopy with a frequency range of 10 Hz. -2 Hz~10 5 The frequency was Hz, the amplitude was 5mV, and lithium dendrites were observed using SEM with an accelerating voltage of 10kV.

[0032] All embodiments and comparative examples use the above-described battery structure and undergo the same performance tests. The specific steps and procedures are as follows. Example

[0033] This embodiment provides a boronene / PVDF composite lithium metal battery anode, the specific raw material ratio of which is as follows: The mass percentage of boronene is 20wt%, PVDF is 78wt%, conductive additive is conductive carbon black with a mass percentage of 2wt%, the particle size of conductive carbon black is 30nm±5nm, the specific surface area is 100m² / g, the purity is 99.8%, the organic solvent is NMP with a purity of 99.95%, and the moisture content is 200ppm. Among them, the degree of hydrogenation of boronene (the ratio of boron atoms to hydrogen atoms in boronene) is 5%, the morphology is two-dimensional sheet-like with a sheet size of 200nm±50nm, a thickness of 3nm±1nm, a purity of 99.6%, and an oxygen content of 0.25%. The XRD pattern shows characteristic diffraction peaks at 2θ=25.3° and 42.1°, and the XPS pattern shows the B 1s peak at 190.8eV and the H 1s peak at 2.4eV. PVDF is lithium-ion grade with a purity of 99.96%, a total metal impurity content of 8 ppm (Fe≤0.8ppm, Na≤0.5ppm, K≤0.6ppm, Cu≤0.4ppm), a molecular weight of 500,000, a PDI of 1.8, a β crystal content of 80%, a melting point of 170℃, a thermal decomposition initiation temperature of 420℃, and can be completely dissolved in NMP within 30 minutes at 60℃. Its preparation method specifically includes the following steps: Step S1, Raw material pretreatment: Place boronene powder in a vacuum drying oven and dry for 12 hours at 100℃ and a vacuum degree ≤5Pa. After drying, pretreated boronene is obtained. Dissolve lithium-ion grade PVDF powder in organic solvent NMP and stir for 4 hours at 70℃ and a stirring speed of 500r / min until PVDF is completely dissolved and there are no obvious particles. Then, a PVDF mother liquor with a mass concentration of 10% is obtained. Cut a 100μm thick lithium metal foil with a purity of 99.9% into 12mm×12mm pieces. Ultrasonically clean it in anhydrous ethanol for 10 minutes at an ultrasonic power of 200W. Then, place it in a vacuum drying oven and dry for 3 hours at 50℃ to obtain a pretreated lithium metal substrate. Transfer it to an inert gas protected glove box for later use. Place the conductive additive in a vacuum drying oven and dry for 6 hours at 90℃. After drying, pretreated conductive additive is obtained. Step S2, Preparation of composite slurry: Pretreated boronene and pretreated conductive additives are added to PVDF mother liquor and stirred for 4 hours at room temperature and stirring speed of 800 r / min. Stirring disperses boronene and conductive additives in PVDF mother liquor. Then, ultrasonic dispersion is carried out for 2 hours at ultrasonic power of 300 W. After ultrasonic dispersion for 30 min, a 10 min pause is required to obtain a uniformly dispersed composite slurry without agglomeration. The viscosity is 1200 mPa·s when tested with a rotational viscometer at 25℃. Step S3, Coating: The composite slurry is uniformly coated onto the pretreated lithium metal substrate using a doctor blade coating method with a doctor blade gap of 20 μm and a coating speed of 10 mm / s. The coating process is carried out in a glove box under inert gas protection, and the thickness is controlled at 10 μm. Step S4, Drying: Place the coated lithium metal substrate in a vacuum drying oven and remove the residual solvent by gradient temperature drying. Dry at 60℃ for 5 hours, and then dry at 120℃ and vacuum degree ≤5a for 12 hours to obtain a semi-finished negative electrode sheet with a smooth surface and no bubbles. Step S5, tableting: Under argon protection, the dried semi-finished negative electrode sheet is tableted using a flatbed tablet press. The tableting pressure is 2MPa and the tableting time is 20min. This increases the bonding tightness between the composite modification layer and the lithium metal substrate. The composite modification layer is formed by coating a composite slurry, and the porosity is controlled at 30%. Step S6, Finished Product Processing: The negative electrode sheet after pressing is placed in a glove box protected by inert gas and cooled to room temperature. After cutting and packaging, the finished product of hydride boronene / PVDF composite lithium metal battery negative electrode is obtained. The negative electrode products prepared above were assembled into CR2032 coin cells, and their electrochemical performance was tested. The test results are as follows: Coulombic efficiency: At a current density of 0.5 mA / cm², with a deposition / stripping capacity of 1 mAh / cm², the coulombic efficiency is 97.8% after 10 cycles, 98.2% after 50 cycles, 98.6% after 100 cycles, 97.2% after 500 cycles, and 96.5% after 1000 cycles. Cyclic stability: At 0.5C rate, the initial discharge capacity is 198 mAh / g, the capacity after 100 cycles is 192 mAh / g with a capacity retention of 96.9%, the capacity after 300 cycles is 185 mAh / g with a capacity retention of 93.4%, the capacity after 500 cycles is 179 mAh / g with a capacity retention of 90.4%, and the capacity after 1000 cycles is 159 mAh / g with a capacity retention of 80.3%. Interface impedance: The interface impedance before cycling was 78Ω, after 100 cycles it was 91Ω, an increase of 16.7%, and after 500 cycles it was 105Ω, an increase of 34.6%. Lithium dendrite suppression effect: After 100 cycles, the surface of the composite anode was observed by SEM. There was no obvious lithium dendrite growth, the surface was flat and uniform, and the composite modification layer showed no cracking or peeling. After 500 cycles, there was still no obvious lithium dendrite on the surface, and the SEI film was uniform and dense with a thickness of about 50nm. Material characterization: XRD patterns showed that characteristic diffraction peaks of both boronene and PVDF appeared simultaneously in the composite modified layer, with no new impurity peaks, proving that the two were well composited and there was no chemical reaction. XPS patterns showed that characteristic peaks of LiF were present in the SEI film (F1s peak at 685.2 eV), indicating that PVDF generated a LiF-stabilized SEI film in situ. Mechanical properties: The tensile strength of the composite modified layer is 320 MPa, the elongation at break is 320%, and the interfacial adhesion is 1.8 N / cm, which can effectively resist lithium dendrite puncture and volume expansion. Example

[0034] This embodiment provides a boronene / PVDF composite lithium metal battery anode, and its preparation method, process, parameters, and equipment are consistent with those of the previous embodiment. After preparation, a finished boronene / PVDF composite lithium metal battery anode is obtained. The difference between this embodiment and Example 1 is in the raw material ratio: the mass percentage of boronene is 15wt%, the mass percentage of PVDF is 85wt%, no conductive additives are used, the organic solvent is DMF, the purity of DMF is 99.9%, and the moisture content is 250ppm. The negative electrode products prepared above were assembled into CR2032 coin cells, and their electrochemical performance was tested. The test results are as follows: Coulombic efficiency: At a current density of 0.5 mA / cm², with a deposition / stripping capacity of 1 mAh / cm², the coulombic efficiency is 97.2% after 10 cycles, 97.8% after 50 cycles, 98.0% after 100 cycles, 96.8% after 500 cycles, and 96.0% after 1000 cycles. Cyclic stability: At 0.5C rate, the initial discharge capacity is 195 mAh / g, the capacity after 100 cycles is 188 mAh / g with a capacity retention of 96.4%, the capacity after 300 cycles is 180 mAh / g with a capacity retention of 92.3%, the capacity after 500 cycles is 174 mAh / g with a capacity retention of 89.2%, and the capacity after 1000 cycles is 156 mAh / g with a capacity retention of 80.0%. Interface impedance: The interface impedance was 82Ω before cycling, and 96Ω after 100 cycles, an increase of 17.1%. After 500 cycles, the interface impedance was 110Ω, an increase of 34.1%. Lithium dendrite suppression effect: After 100 cycles, SEM observation showed no obvious lithium dendrite growth on the surface of the composite anode, the surface was smooth, and the composite modification layer was tightly bonded to the lithium metal substrate. After 500 cycles, there were still no obvious lithium dendrites on the surface, the SEI film was uniform, and the thickness was about 55 nm. Material characterization: XRD patterns showed good composite formation of borane and PVDF with no impurity peaks. XPS patterns showed characteristic LiF peaks in the SEI film, indicating that PVDF forms a stable SEI film in situ. Mechanical properties: The tensile strength of the composite modified layer is 300 MPa, the elongation at break is 350%, and the interfacial adhesion is 1.6 N / cm, which can effectively buffer volume expansion. Example

[0035] This embodiment provides a boronene / PVDF composite lithium metal battery anode, and its preparation method, process, parameters, and equipment are consistent with those of the previous embodiment. After preparation, a finished boronene / PVDF composite lithium metal battery anode is obtained. The difference between this embodiment and Example 1 is in the raw material ratio: the mass percentage of boronene is 25wt%, the mass percentage of PVDF is 72wt%, the conductive additive is carbon nanotubes with a mass percentage of 3wt%, the organic solvent is DMSO with a purity of 99.9%, and the moisture content is 220ppm. The negative electrode products prepared above were assembled into CR2032 coin cells, and their electrochemical performance was tested. The test results are as follows: Coulombic efficiency: At a current density of 0.5 mA / cm², with a deposition / stripping capacity of 1 mAh / cm², the coulombic efficiency is 98.0% after 10 cycles, 98.5% after 50 cycles, 99.0% after 100 cycles, 97.5% after 500 cycles, and 96.8% after 1000 cycles. Cyclic stability: At 0.5C rate, the initial discharge capacity is 200 mAh / g, the capacity after 100 cycles is 195 mAh / g with a capacity retention of 97.5%, the capacity after 300 cycles is 188 mAh / g with a capacity retention of 94.0%, the capacity after 500 cycles is 182 mAh / g with a capacity retention of 91.0%, and the capacity after 1000 cycles is 162 mAh / g with a capacity retention of 81.0%. Interface impedance: The interface impedance before cycling was 75Ω, after 100 cycles it was 87Ω, an increase of 16.0%, and after 500 cycles it was 102Ω, an increase of 36.0%. Lithium dendrite suppression effect: After 100 cycles, SEM observation showed that the composite anode surface was flat and there was no lithium dendrite growth. The composite modification layer was dense. After 500 cycles, there were still no lithium dendrites on the surface. The SEI film was uniform and dense with a thickness of about 48nm. Material characterization: XRD patterns showed that hydride boronene, PVDF and carbon nanotubes were well combined and there were no impurity peaks. XPS patterns showed that the characteristic peak of LiF in the SEI film was obvious, indicating that the SEI film was stable. Mechanical properties: The tensile strength of the composite modified layer is 350 MPa, the elongation at break is 310%, and the interfacial adhesion is 2.0 N / cm, indicating that the puncture resistance and interfacial stability are optimal. Example

[0036] This embodiment provides a boronene / PVDF composite lithium metal battery anode. The raw material ratio, preparation method, process, parameters, and equipment are consistent with those of the previous embodiment. The difference between this embodiment and Example 1 is that the degree of hydrogenation of boronene is changed to 10%, 40%, and 80%, respectively, to prepare three different finished products of boronene / PVDF composite lithium metal battery anodes. The prepared anode products are assembled into CR2032 coin cells and are designated as Example 4-1 (degree of hydrogenation 10%), Example 4-2 (degree of hydrogenation 40%), and Example 4-3 (degree of hydrogenation 80%), respectively. Electrochemical performance tests are performed, and the test results are shown in Table 1 below. Table 1 - Schematic comparison of battery samples prepared from boronene with different degrees of hydrogenation Example 4-1 10% 97.2 85.6 98 The surface has a small amount of lithium dendrites, and the composite modification layer is slightly cracked. Example 4-2 40% 98.8 90.1 89 The surface is free of lithium dendrites, and the composite modification layer is smooth and crack-free. Example 4-3 80% 98.1 88.7 93 No obvious lithium dendrites were found on the surface, and the composite modification layer was free of cracks. According to Table 1, the composite anode exhibits the best overall performance when the degree of hydrogenation of boronene is 30% to 60%. Too low a degree of hydrogenation leads to insufficient lithiophilicity, poor stability, and the formation of a small amount of lithium dendrites. Too high a degree of hydrogenation reduces ionic conductivity and causes an increase in interfacial impedance.

[0037] Comparative Example 1 This comparative example provides a finished negative electrode product, namely a pure PVDF-modified lithium metal negative electrode, which differs from Example 1 in that: only lithium-ion grade PVDF from Example 1 is used as the modification layer, without boron hydride and conductive additives. The coating, drying, and pressing processes and parameters are the same as in Example 1. The thickness of the modification layer is controlled at 10 μm ± 0.1 μm, and the porosity is 30%. The negative electrode products prepared above were assembled into CR2032 coin cells, and their electrochemical performance was tested. The test results are as follows: Coulomb efficiency: At a current density of 0.5 mA / cm², the coulomb efficiency is 94.2% after 100 cycles, 88.5% after 500 cycles, and 82.1% after 1000 cycles. Cycling stability: At a 0.5C rate, the capacity retention rate is 65.3% after 500 cycles and 58.7% after 1000 cycles; Interface impedance: The interface impedance was 85Ω before cycling and 132Ω after 100 cycles, representing an increase of 55.3%. Lithium dendrite suppression effect: After 100 cycles, SEM observation showed obvious needle-like lithium dendrites on the surface, with a length of about 2~5μm. The modified layer showed slight cracking. After 500 cycles, the lithium dendrites pierced the modified layer, and a large area of ​​the surface peeled off. Mechanical properties: The tensile strength of the modified layer is 85 MPa, the elongation at break is 330%, and the interfacial adhesion is 0.9 N / cm.

[0038] Comparative Example 2 This comparative example provides a finished negative electrode product, namely a pure boronene-modified lithium metal negative electrode, which differs from Example 1 in that: only the boronene from Example 1 is used as the modification layer, without PVDF and conductive additives, and a 10% (w / w) boronene slurry is prepared using NMP as the organic solvent. The coating, drying, and pressing processes and parameters are the same as in Example 1. The thickness of the modification layer is controlled at 10 μm ± 0.1 μm, and the porosity is 30%. The negative electrode products prepared above were assembled into CR2032 coin cells, and their electrochemical performance was tested. The test results are as follows: Coulomb efficiency: At a current density of 0.5 mA / cm², the coulomb efficiency is 94.8% after 100 cycles, 89.2% after 500 cycles, and 83.5% after 1000 cycles. Cycling stability: At a 0.5C rate, the capacity retention rate is 67.8% after 500 cycles and 60.2% after 1000 cycles; Interface impedance: The interface impedance before cycling was 72Ω, and after 100 cycles, the interface impedance was 118Ω, an increase of 63.9%. Lithium dendrite suppression effect: After 100 cycles, there are no obvious needle-like lithium dendrites on the surface, but local agglomerated lithium deposition occurs. After 50 cycles, obvious cracking of the modified layer occurs. After 100 cycles, the cracking intensifies and peeling occurs. Mechanical properties: The tensile strength of the modified layer is 310 MPa, the elongation at break is 85%, and the interfacial adhesion is 0.8 N / cm.

[0039] Comparative Example 3 This comparative example provides a finished negative electrode product, namely a lithium metal negative electrode modified with PVDF and LiAlO2 composite. The difference from Example 1 is that lithium-ion grade PVDF, LiAlO2, and conductive additives are used as the modification layer. Boronene is not used. The mass percentage of PVDF is 78 wt%, the mass percentage of LiAlO2 is 20 wt%, the particle size of LiAlO2 is 50~100 nm, and the purity is 99.5%. The conductive additive is conductive carbon black with a mass percentage of 2 wt%. The coating, drying, and pressing processes and parameters are the same as in Example 1. The thickness of the modification layer is controlled at 10 μm ± 0.1 μm, and the porosity is 30%. The negative electrode products prepared above were assembled into CR2032 coin cells, and their electrochemical performance was tested. The test results are as follows: Coulomb efficiency: At a current density of 0.5 mA / cm², the coulomb efficiency is 94.5% after 100 cycles, 88.8% after 500 cycles, and 82.7% after 1000 cycles. Cycling stability: At a 0.5C rate, the capacity retention rate is 68.5% after 500 cycles and 61.3% after 1000 cycles; Interface impedance: The interface impedance was 80Ω before cycling and 125Ω after 100 cycles, representing an increase of 56.2%. Lithium dendrite suppression effect: After 100 cycles, a small number of needle-like lithium dendrites appeared on the surface, with a length of about 1~3μm. The composite modification layer did not show obvious cracking, but slight peeling occurred at the interface. Mechanical properties: The tensile strength of the modified layer is 120 MPa, the elongation at break is 220%, and the interfacial adhesion is 1.1 N / cm.

[0040] Specifically, by comparing the performance of the above embodiments and comparative examples, it can be seen that: Embodiments 1, 2, and 3 are comprehensively superior to Comparative Example 1 (pure PVDF) and Comparative Example 2 (pure boronene) in all key indicators such as coulombic efficiency, cycle stability, interface impedance control, and lithium dendrite suppression. PVDF (Comparative Example 1) or boronene (Comparative Example 2) alone cannot simultaneously meet the requirements of suppressing dendrites and buffering volume expansion, resulting in rapid decay of cycle performance. This proves that a single material cannot simultaneously achieve rigidity and flexibility, ionic conductivity and film stability, indicating that the synergistic effect of boronene and PVDF is significant. This invention can solve the performance defects of single materials and existing composite systems. Examples 1, 2, and 3 also outperformed Comparative Example 3 (PVDF / LiAlO2), demonstrating that boronene, as a functional filler, has superior combined advantages in lithiophilicity and conductivity compared to existing fillers. Boronene, with its excellent lithiophilicity, two-dimensional structure, and electronic conductivity, exhibits advantages in dendrite suppression and interface stability. Examples 1 and 3 (containing conductive additives) outperformed Example 2 (without conductive additives), indicating that a small amount of conductive additive helps to further improve performance. Example 4 demonstrates that the optimal degree of hydrogenation is between 30% and 60%, revealing the influence of hydrogenation degree on performance.

[0041] In summary, this invention addresses the problems of lithium dendrite growth, volume expansion, SEI film instability, and performance limitations of single modifying materials in existing lithium metal anodes. It designs a boron hydride / PVDF composite lithium metal battery anode, utilizing the complementary performance advantages of boron hydride and PVDF to construct a composite modifying layer with high mechanical strength, high flexibility, and high conductivity. Then, through controlled raw material ratios, pretreatment processes, coating, drying, and pressing operations, it achieves efficient suppression of lithium dendrites, long-term stability of the electrode interface, and significant optimization of battery cycle performance.

[0042] The above description is merely a specific embodiment of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.

Claims

1. A method for preparing a boronide / PVDF composite lithium metal battery anode, characterized in that, Specifically, the following steps are included: Step S1, Raw material pretreatment: Borobenzene powder is placed in a vacuum drying oven. After the drying operation, pretreated borobenzene is obtained. Lithium-ion grade PVDF powder is dissolved in an organic solvent and stirred until PVDF is completely dissolved and there are no obvious particles to obtain PVDF mother liquor. Lithium metal foil is cut into a preset size, ultrasonically cleaned with anhydrous ethanol, and dried in a vacuum drying oven to obtain pretreated lithium metal substrate. It is then transferred to a glove box protected by inert gas for later use. Conductive additive is placed in a vacuum drying oven and dried to obtain pretreated conductive additive. Step S2, preparation of composite slurry: add pretreated boronene and pretreated conductive additive to PVDF mother liquor, stir to disperse boronene and conductive additive in PVDF mother liquor, and then disperse by ultrasonication to obtain a uniformly dispersed composite slurry without agglomeration. Step S3, Coating: The composite slurry is uniformly coated onto the surface of the pretreated lithium metal substrate by means of scraper coating, spraying or dipping. The coating process is carried out in a glove box protected by inert gas. Step S4, Drying: Place the coated lithium metal substrate into a vacuum drying oven and use a gradient temperature drying method to remove residual solvent, so as to obtain a semi-finished negative electrode sheet with a smooth surface and no bubbles. Step S5, tableting: Under inert gas protection, the dried semi-finished negative electrode sheet is tableted using a flatbed tablet press to increase the bonding tightness between the composite modification layer and the lithium metal substrate. The composite modification layer is formed by coating a composite slurry. Step S6, Finished Product Processing: The negative electrode sheet after compression is placed in a glove box protected by inert gas and cooled to room temperature. After cutting and packaging, the finished product of hydride boronene / PVDF composite lithium metal battery negative electrode is obtained.

2. The preparation method according to claim 1, characterized in that, The raw material pretreatment in step S1 specifically includes pretreatment of boronene, preparation of PVDF mother liquor, pretreatment of lithium metal substrate, and pretreatment of conductive additives, specifically including: Pretreatment of hydroborene: The hydroborene powder is placed in a vacuum drying oven and dried for 8h to 24h at a temperature of 60℃~120℃ and a vacuum degree of ≤10Pa to remove the moisture and impurities adsorbed on the surface of the hydroborene powder. After the drying operation is completed, the pretreated hydroborene is obtained. Preparation of PVDF mother liquor: Lithium-ion grade PVDF powder is dissolved in an organic solvent and stirred for 2 to 6 hours at a temperature of 60℃ to 80℃ and a stirring speed of 300 r / min to 800 r / min. After stirring until the PVDF is completely dissolved and there are no obvious particles, it is allowed to stand for 1 to 2 hours to prepare a PVDF mother liquor with a mass concentration of 5% to 20%. Lithium metal substrate pretreatment: The lithium metal foil is cut into a preset size and ultrasonically cleaned in anhydrous ethanol for 5 min to 15 min under an ultrasonic power of 100W to 300W to remove the oxide layer and oil on the surface of the lithium metal foil. Then it is placed in a vacuum drying oven and dried at a temperature of 40℃ to 60℃ for 2 h to 4 h. After drying, the pretreated lithium metal substrate is obtained and transferred to a glove box protected by inert gas for later use. Conductive additive pretreatment: The conductive additive is placed in a vacuum drying oven and dried at a temperature of 80℃~100℃ for 4h~8h to remove the surface moisture of the conductive additive. After the drying operation is completed, the pretreated conductive additive is obtained.

3. The preparation method according to claim 1, characterized in that, The preparation of the composite slurry in step S2 specifically includes: adding pretreated boronene and pretreated conductive additives to the PVDF mother liquor, stirring for 2 to 6 hours at room temperature and a stirring speed of 500 r / min to 1000 r / min, and dispersing the boronene and conductive additives in the PVDF mother liquor. Then, ultrasonically disperse the slurry for 1 to 3 hours at an ultrasonic power of 100 W to 500 W, with a 10-minute pause after every 30 minutes of ultrasonic dispersion. After ultrasonic dispersion, a uniformly dispersed composite slurry without agglomeration is obtained. The room temperature is 20 to 25°C.

4. The preparation method according to claim 1, characterized in that, The coating process in step S3 specifically includes: uniformly coating the composite slurry onto the surface of the pretreated lithium metal substrate by means of scraper coating, spraying or dipping. The coating process is carried out in a glove box under inert gas protection. The thickness of the composite modification layer after coating is controlled at 1μm~20μm. Specifically, when using a scraper for coating, the scraper gap is 10μm~40μm and the coating speed is 5mm / s~15mm / s. When using a spray gun, the spray gun pressure is 0.1MPa~0.3MPa, the spraying distance is 10cm~20cm, and the spraying speed is 8mm / s~12mm / s. When using a dip coating, the immersion time is 10s~30s and the lifting speed is 5mm / s~10mm / s.

5. The preparation method according to claim 1, characterized in that, The gradient temperature drying in step S4 specifically includes: Drying at 60℃~80℃ for 4h~6h removes most of the solvent; Drying at 100℃~150℃ and vacuum degree ≤10Pa for 8h~18h is used to remove residual solvent and obtain a semi-finished negative electrode sheet with a smooth surface and no bubbles. During the drying process, the temperature rise rate is controlled at 5℃ / min to 10℃ / min.

6. The preparation method according to claim 1, characterized in that, In step S5, the tableting pressure is 0.5MPa~5MPa, the tableting time is 10min~30min, and the porosity of the composite modified layer after tableting is controlled at 10%~50%.

7. The preparation method according to claim 2, characterized in that, The organic solvent is one or more of N-methylpyrrolidone, dimethylformamide, or dimethyl sulfoxide.

8. A boronene / PVDF composite lithium metal battery anode, characterized in that, The negative electrode is prepared by the preparation method according to any one of claims 1-7, wherein the negative electrode comprises a lithium metal substrate and a composite modification layer coated on the surface of the lithium metal substrate, the thickness of the composite modification layer is 1μm~20μm, the porosity is 10%~50%, and the pore size is 50nm~500nm.

9. The boronide / PVDF composite lithium metal battery anode according to claim 8, characterized in that, The composite modification layer is composed of boronene, PVDF and conductive additives. The boronene has a mass percentage of 15wt% to 25wt%, the PVDF has a mass percentage of 72wt% to 85wt%, and the conductive additive has a mass percentage of 0wt% to 3wt%. The conductive additive is either conductive carbon black or carbon nanotubes.

10. The application of a boronide / PVDF composite lithium metal battery anode prepared by the preparation method according to any one of claims 1-7 in the field of lithium metal batteries, characterized in that, It is used to suppress lithium dendrite growth, alleviate lithium metal volume expansion, and stabilize the solid electrolyte interface film during the charging and discharging process of lithium metal batteries.